Father’s Presence and Involvement in Child Development: A Survey to Develop A Fatherhood Module - Siti Nubailah Mohd Yusof; Haslee Sharil Lim Abdullah; Abdul Rashid Abdul Aziz (Human Resources Management Academic Research Society, 2024)
International Journal of Academic Research in Business and Social Sciences, Volume 13 Issue 13 Page (32–42)